DNA/AuNP-graphene back-gated field effect transistor as a biosensor for lead (II) ion detection - Chee, L.H. (Institute of Electrical and Electronics Engineers Inc., 2017)
Lead is a very toxic substance that causes metabolic disruption by mimicking the chemical profile of other important ions in the human body. The current technique of determining the presence of lead in drinkable water are simply too expensive to be implemented for large-scale real time monitoring. As an alternative, a sensor based on graphene field effect transistor is developed. The graphene layer itself is decorated with gold nanoparticle (AuNP) and it acts as a sensing medium while guanine-rich deoxyribonucleic acid (DNA) that is attached to the AuNP acts as a chemical probe. The guanine-rich DNA forms G-quadruplex when exposed to lead ions and thus changes the overall charge on the surface of the graphene. The changes can be observed via I-V measurement of the sensor. The fabricated sensors are capable of detecting lead ions even at 20 nM concentration. Such a sensor is scalable and can offer a cheap and effective option for monitoring the quality of water in real-time. © 2017 IEEE.